2017
DOI: 10.1038/s41598-017-09990-9
|View full text |Cite
|
Sign up to set email alerts
|

FLO5 gene controls flocculation phenotype and adhesive properties in a Saccharomyces cerevisiae sparkling wine strain

Abstract: Flocculation is an important feature for yeast survival in adverse conditions. The natural diversity of flocculating genes in Saccharomyces cerevisiae can also be exploited in several biotechnological applications. Flocculation is mainly regulated by the expression of genes belonging to the FLO family. These genes have a similar function, but their specific contribution to flocculation ability is still unclear. In this study, the distribution of FLO1, FLO5 and FLO8 genes in four S. cerevisiae wine strains was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 64 publications
0
19
0
1
Order By: Relevance
“…Cheats could therefore reap the benefits of flocculating without paying the cost of expressing FLO1 [39]. In fact, there is evidence that lossof-function mutants can occur in and spread through natural populations of yeast expressing the FLO1 homologue, FLO5 [40]. This provides support for the prediction that cheating mutants can only spread in multicellular groups that have formed through aggregation, and not through clonal development.…”
Section: Why Is Group Formation Important?mentioning
confidence: 89%
“…Cheats could therefore reap the benefits of flocculating without paying the cost of expressing FLO1 [39]. In fact, there is evidence that lossof-function mutants can occur in and spread through natural populations of yeast expressing the FLO1 homologue, FLO5 [40]. This provides support for the prediction that cheating mutants can only spread in multicellular groups that have formed through aggregation, and not through clonal development.…”
Section: Why Is Group Formation Important?mentioning
confidence: 89%
“…A more recent study with a high flocculant S. cerevisiae strain showed that FLO5 plays an important role in cell-surface adhesion. In fact, the deletion of FLO5 caused a strong reduction in flocculation capacity when compared with the deletion of FLO1 [64]. Govender et al (2008) suggested a strategy for the optimization of flocculation through the controlled expression of FLO1, FLO5, and FLO11 in S. cerevisiae [65].…”
Section: Flocculationmentioning
confidence: 99%
“…The FLO gene family can be divided into two groups. The first group-FLO1, FLO5, FLO9, and FLO10-share considerable sequence homology and are subtelomeric genes that code for proteins responsible for cell to cell adhesion and form aggregates of many cells known as flocs (Soares 2011;Di Gianvito et al 2017). These lectin-like proteins recognize and bind to α-mannan residues (receptors) of neighboring cells (Verstrepen et al 2003).…”
Section: Yeast Adhesionmentioning
confidence: 99%